Novel Synthetic and Natural Therapies for Traumatic Brain Injury - Battaglini, Denise; Siwicka-Gieroba, Dorota; Rocco, Patricia R.; Cruz, Fernanda Ferreira; Silva, Pedro Leme; Dabrowski, Wojciech; Brunetti, Iole; Patroniti, Nicolò; Pelosi, Paolo; Robba, Chiara (Current Neuropharmacology, 2021)
Traumatic brain injury (TBI) is a major cause of disability and death worldwide. The initial mechanical insult results in tissue and vascular disruption with hemorrhages and cellular necrosis that is followed by dynamic secondary brain damage that presumably results in additional destruction of the brain. In order to minimize deleterious consequences of the secondary brain damage- such as inflammation, bleeding or reduced oxygen supply. The old concept of the -staircase approach- has been updated in recent years by most guidelines and should be followed as it is considered the only validated approach for the treatment of TBI. Besides, a variety of novel therapies have been proposed as neuroprotectants. The molecular mechanisms of each drug involved in the inhibition of secondary brain injury can result as a potential target for the early and late treatment of TBI. However, no specific recommendation is available on their use in the clinical setting. The administration of both synthetic and natural compounds, which act on specific pathways involved in the destructive processes after TBI, even if usually employed for the treatment of other diseases, can show potential benefits. This review represents a massive effort towards current and novel therapies for TBI that have been investigated in both pre-clinical and clinical settings. This review aims to summarize the advancement in therapeutic strategies based on specific and distinct -target of therapies-: brain edema, ICP control, neuronal activity and plasticity, anti-inflammatory and immunomodulatory effects, cerebral autoregulation, antioxidant properties, and future perspectives with the adoption of mesenchymal stromal cells.
Keywords: Pharmacology